Penggunaan Knowledge Capture Untuk Promosi Sbu Marine Services Melalui Pendekatan Soft System Methodology (SSM) - Heidi Vena Br Gintings; Effy Zalfiana Rusfiani; Rchma Fitriati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Efficient marketing is essential to attract customers and maintain a good reputation in the maritime services sector. SBU Marine Services faces a number of difficulties in managing promotion-related knowledge effectively. By using a Soft System Methodology (SSM) approach, this research tries to record and capture promotional knowledge at SBU Marine Services. To improve the quality and effectiveness of a company's promotional efforts, it is hoped that a deeper and more methodical understanding of the promotional process can be achieved through the implementation of SSM. The findings of this research are expected to have a major impact on improving marketing tactics and strengthening SBU Marine Services' position in the marine services industry.